Menumbuhkan Budaya Literasi pada Anak-Anak Pekerja Migran Indonesia (PMI) di SB Puchong Perdana Malaysia - Djakfar Musthafa, Fera Andriani; Rahmawati, Saadah; Saadah, Latifatus (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Every child should be literate as a foundation for their intellectual development in the future. Unfortunately, due to certain conditions, many children of Indonesian Migrant Workers (PMI) in Malaysia do not have broad opportunities to develop their literacy skills. Therefore, STAI Syaichona Moh. Cholil Bangkalan, through its International KKN (Community Service Program), sent a delegation to Malaysia to promote literacy programs for PMI children. The goal is to equip PMI children with reading and writing skills, enabling them to catch up in education and social development. This community service was carried out at SB Puchong Perdana, Selangor, Malaysia, through counseling, intensive mentoring, the provision of educational books, interactive storytelling sessions, the establishment of reading spaces, and educational games. The program was also documented and evaluated to monitor its sustainability. The outcomes of this program included improved reading and writing skills, increased confidence in academic and social competition, expanded opportunities for higher education, strengthened national identity, reduced dropout rates, and minimized social vulnerability.